Stability analysis of the extended Kalman filter for Permanent Magnet Synchronous Motor - Taibi, Djamel; Titaouine, Abdenacer; Benchabane, Fateh; Bennis, Ouafae (Journal of Applied Engineering Science & Technology, 2015)
This paper presents a sensorless direct field oriented control fed interior permanent magnet synchronous motor (IPMSM) by using a known mathematical tool. The Kalman filter is an observer for linear and non-linear systems and is based on the stochastic intromission, in others words, noise. It is a question of studying the state and measurement noise covariance matrices Q and R on the stability of the Extended Kalman Filter. This last is used for the d, q stator current, mechanical speed, rotor position, stator resistance and the load torque estimation. The simulation tests carried out on Matlab Simulink showed that the matrix R improves much more quality of the estimated states while the matrix Q allows the improvement of the estimation process convergence.
Keywords: Permanent magnet synchronous machine, Direct filed oriented control, Extended Kalman filter, Estimation